Health Promotion Model for the Elderly in Flood with a mudslide area in Thailand - Muangkaew, Prapaporn; Thojampa, Somsak (International Journal of Psychosocial Rehabilitation, 2021)
The health problems of the elderly that will be a contributing factor to the illness and the deterioration of the body  This research aimed to study a health promotion model for the elderly in flood area with a mudslide at Uttaradit Province, Thailand